2022
DOI: 10.1186/s40643-022-00588-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of explant type (leaf, stem) and 2,4-D concentration on callus induction: influence of elicitor type (biotic, abiotic), elicitor concentration and elicitation time on biomass growth rate and costunolide biosynthesis in gazania (Gazania rigens) cell suspension cultures

Abstract: Gazania rigens(L.) Gaertn. (Asteraceae) is a medicinal plant with high ornamental potential and use in landscaping. The therapeutic potential of sesquiterpene lactones (SLs) as plant natural products for pharmaceutical development has gained extensive interest with costunolide (chemical name: 6E,10E,11aR-6,10-dimethyl-3-methylidene-3a,4,5,8,9,11a-hexahydrocyclodeca[b]furan-2-one) used as a popular herbal remedy due to its anti-cancer, antioxidant, anti-inflammatory, anti-microbial, anti-allergic, and anti-diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…The lowest total phenolic content was found in This result shows that it affects not only the callus biomass but also the total phenolic content in the regions to which the genotypes are grown. Mahood et al (2022) showed that the type of explant and 2,4-D concentration affected the type and morphology of callus formation. These findings are in agreement with that reported by Castro et al (2016) in the study on callus induction and phenolic component production from Byrsonima verbascifolia.…”
Section: Resultsmentioning
confidence: 99%
“…The lowest total phenolic content was found in This result shows that it affects not only the callus biomass but also the total phenolic content in the regions to which the genotypes are grown. Mahood et al (2022) showed that the type of explant and 2,4-D concentration affected the type and morphology of callus formation. These findings are in agreement with that reported by Castro et al (2016) in the study on callus induction and phenolic component production from Byrsonima verbascifolia.…”
Section: Resultsmentioning
confidence: 99%
“…However, no elicitation method is suitable for all culture systems. The elicitation efficiency is affected by several factors, such as elicitor types, elicitor concentrations, elicitation treatment time, and duration [30]. Therefore, the selection of an appropriate elicitation strategy is essential for improving the production of useful metabolites.…”
Section: Optimization Of Ye Elicitationmentioning
confidence: 99%